The Effect of Paired Passing Training on the Lower Passing Ability - Yulda Nikodemus Manurung; Dewi Maya Sari (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This study aims to determine the effect of paired passing exercises on the lower passing ability of Bintang Junior soccer school students aged 10-12 years. The type of research is experimental with the design